2009
DOI: 10.1295/polymj.pj2009147
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Preparation and Properties of Sol–Gel Molecularly Imprinted Polymer Based on Tetramethoxysilane and Methyltrimethoxysilane for Recognized Sulfonamides

Abstract: The synthesis of a molecularly imprinted polymer (MIP) composed of tetramethoxysilane (TMOS) and methyltrimethoxysilane (MTMOS) for recognized sulfonamides by sol-gel process has been investigated. The MIP's preparation conditions, the H 2 O/Si molar ratios (R), pH value of competition solution, calcination temperature, and the TMOS and MTMOS molar fractions are discussed. Adsorption and selectivity in different pH solutions were determined by competition experiments between the MIP template (sulfamethazine, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Efforts to employ MIPs in assays have extended well beyond the large volume of literature focused upon MIPSE, most notably CE and CEC, and LC . In contrast to the 1990s and early 2000s, the proportion of studies devoted to, or heavily dependent upon, LC has reduced significantly.…”
Section: Applicationsmentioning
confidence: 99%
“…Efforts to employ MIPs in assays have extended well beyond the large volume of literature focused upon MIPSE, most notably CE and CEC, and LC . In contrast to the 1990s and early 2000s, the proportion of studies devoted to, or heavily dependent upon, LC has reduced significantly.…”
Section: Applicationsmentioning
confidence: 99%
“…Furthermore, the template molecule (thiamphenicol) is a small molecule (< 1 nm) and aperture of pore is less than 4 nm in P1_MIP, it may be thought that the more effective adsorption capacity could be occured. On the other hand, the smaller size distribution could raise the selectivity and increase the imprinting factor value for the polymer [13]. For adsorption/desorption isotherms studies, it was revealed more about the MIPs porosity characteristics.…”
Section: Physical Characterizationsmentioning
confidence: 99%
“…Then the mesopores continue filling by capillary condensation and once again adsorption levels off as the mesopores are filled. During desorption, as pressure is lowered, the mesopores are emptied by capillary evaporation, but when capillary condensation and capillary evaporation do not take place at the same pressure, a hysteresis loop is created [13,15]. However, hysteresis loop obtained was much steeper for P2_NIP compared to P1_MIP.…”
Section: Physical Characterizationsmentioning
confidence: 99%